Isolation and In Silico Anti-COVID-19 Main Protease (Mpro) Activities of Flavonoids and a Sesquiterpene Lactone from Artemisia sublessingiana - Roza I. Jalmakhanbetova; Yerlan M. Suleimen; Masayoshi Oyama; Eslam B. Elkaeed; Ibrahim. H. Eissa; Raigul N. Suleimen; Ahmed M. Metwaly; Margarita Yu. Ishmuratova (Journal of Chemistry)
The emergence of the COVID-19 pandemic declared the huge need of humanity for new and effective antiviral drugs. The reported antimicrobial activities of Artemisia sublessingiana encouraged us to investigate the ethanol extract of its aerial parts which led to the isolation of six flavonoids and a sesquiterpenoid. The structures of the isolated compounds were elucidated by EI-MS, 1D, and 2D NMR spectroscopic methods to be (1) eupatilin, (2) 3′,4′-dimethoxyluteolin, (3) 5,7,3′-trihydroxy-6,4′,5′-trimethoxyflavone, (4) hispidulin, (5) apigenin, (6) velutin, and (7) sesquiterpene lactone 8α,14-dihydroxy-11,13-dihydromelampolide. The isolated compounds were in silico examined against the COVID-19 main protease (Mpro) enzyme. Compounds 1–6 exhibited promising binding modes showing free energies ranging from −6.39 to −6.81 (kcal/mol). The best binding energy was for compound 2. The obtained results give hope of finding a treatment for the COVID-19 pandemic.